2011
DOI: 10.1371/journal.pone.0020462
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Flexibility and Clinical Severity in Eating Disorders

Abstract: ObjectivesThe aim of this study was to explore cognitive flexibility in a large dataset of people with Eating Disorders and Healthy Controls (HC) and to see how patient characteristics (body mass index [BMI] and length of illness) are related to this thinking style.MethodsA dataset was constructed from our previous studies using a conceptual shift test - the Brixton Spatial Anticipation Test. 601 participants were included, 215 patients with Anorexia Nervosa (AN) (96 inpatients; 119 outpatients), 69 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
167
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(182 citation statements)
references
References 18 publications
9
167
1
5
Order By: Relevance
“…Further studies are needed to longitudinally explore the development of eating psychopathology, its risk factors, and inflexible adherence to eating rules. Given the large body of evidence derived from neuropsychological studies on inflexible thinking style in disordered eating patients [23,24,22], the findings from the current study should also be corroborated through experimental designs using neuropsychological tasks, which overcome the limitation of using selfreport measures. Besides, more work is needed to confirm this study's findings on patients with eating disorders.…”
Section: It Is Increasingly Recognized That Adolescence Is a Criticalmentioning
confidence: 83%
See 1 more Smart Citation
“…Further studies are needed to longitudinally explore the development of eating psychopathology, its risk factors, and inflexible adherence to eating rules. Given the large body of evidence derived from neuropsychological studies on inflexible thinking style in disordered eating patients [23,24,22], the findings from the current study should also be corroborated through experimental designs using neuropsychological tasks, which overcome the limitation of using selfreport measures. Besides, more work is needed to confirm this study's findings on patients with eating disorders.…”
Section: It Is Increasingly Recognized That Adolescence Is a Criticalmentioning
confidence: 83%
“…This may occur when the individual blindly follows rigid eating rules, without meeting internal and external cues, and consequently engages in disordered eating behaviours with possible damaging consequences [11]. A large number of studies using neuropsychological tasks have been gathering support that eating disorders patients, especially with restrictive eating patterns, present an inflexible cognitive style [22][23][24]. This pattern of poor flexibility of thinking has been identified as a vulnerability trait, as being associated with the maintenance of the disorder, and with poorer treatment outcomes [25].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings-even in light of these limitations-may have implications for the therapy and management of women with eating disorders. Executive function deficits have been cited as relevant to treatment resistance in this population, 40 and to the extent that such deficits are related to anxiety symptoms, the latter may be particularly targeted when treating women with eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For [76,77]. However, it is important to bear in mind that similar cognitive biases have been found in otherwise healthy individuals experiencing starvation [78], therefore it is possible that the similarities between ASD and AN are a temporary result of the eating disorder, rather than a shared underlying cause. Case studies suggest that some women with AN may in fact have an undiagnosed ASD, with self-reported ASD symptoms, based on descriptions of behaviour from before the development of their eating disorder, reaching levels sufficient for an ASD diagnosis [79].…”
Section: Anorexia Nervosamentioning
confidence: 96%